Makkobar Tradition at Marriage in Batang Baruhar Jae Perspective of Social Reconstruction - Silvi Tabah Hati (Edumaspul: Jurnal Pendidikan, 2023)
Abstract Makkobar or marata-ata is a traditional convention that regulates and provides examples. All elements of the family who are considered as important relatives must indeed be Makkobar. In this case, the community believes that the sacredness contained in the Makkobar Tradition is by acting as a bridge and a requirement for people who have a marriage intention. This paper uses Symbolic Interaction Theory. This research was conducted in Batang Baruhar Julu Village, North Padang Lawas Regency. The research informants were traditional elders, village heads and brides, totaling 32 couples. This research was conducted for approximately 2 months, starting from December 3 to January 28. All approaches taken by researchers are descriptive (qualitative) structured from observation, interviews and documentation. The results of the study illustrate that the combination of traditions that exist in the Makkobar Tradition gives meaning to symbols or objects as text requirements in carrying out kemanten. While Makkobar has three meanings, including; The Value of Effective Communication, the Values of Islamic Teachings and forming a Sakinah Mawaddah Wa Rahmah Family and communicative actions in Makkobar. In View of Social Reconstruction Makkobar Tradition has Philosophical values, stability of social status, and understanding of Islamic Law. However, seeing as time goes by there has been a shift from time to time, both from the agreement process to the event procession. First, the mention of the honest amount. Second, the agreement process. Third, the party that carries out the tradition. Keywords : Tradition, Makkobar, Social Reconstruction. TRADISI MAKKOBAR PADA PERNIKAHAN DI BATANG BARUHAR JAE PERSFEKTIF REKONTRUKSI SOSIAL Abstrak Makkobar atau marata-ata merupakan konvensi traditif yang mengatur dan memberikan keteladanan. Semua unsur keluarga yang dianggap sebagai kerabat penting memang harus Makkobar. Dalam hal ini masyarakat masyarakat meyakini bahwa sakralitas yang terdapat dalam Tradisi Makkobar adalah dengan cara sebagai jembatan dan syarat masyarakat yang mempunyai hajat perkawinan. Tulisan ini menggunakan Teori Interaksi Simbolik. Penelitian ini dilakukan di Desa Batang Baruhar Julu, Kabupaten Padang Lawas Utara. Informan penelitian merupakan para tetuah adat, Kepala Desa dan para pengantin yang berjumlah 32 Pasangan. Penelitian ini dilakukan selama kurang lebih 2 Bulan, yang dimulai pada tanggal 03 Desember hingga 28 Januari. Semua pendekatan yang dilakukan peneliti yaitu bersifat deskriptif (Kualitatif) yang terstruktur dari observasi, wawancara dan dokumentasi. Hasil Penelitian memberikan gambaran bahwa Perpaduan tradisi yang ada dalam Tradisi Makkobar memberikan makna terhadap simbol atau benda sebagai teks syarat dalam melakukan kemanten. Sedangkan Makkobar memiliki tiga makna, diantaranya; Nilai Komunikasi Efektif, Nilai-Nilai Ajaran Islam dan membentuk Keluarga Sakinah Mawaddah Wa Rahmah serta tindak komunikatif dalam Makkobar. Pada Pandangan Rekontruksi Sosial Tradisi Makkobar memiliki nilai-nilai Filosofis, stabilitas status sosial, dan memahami Hukum Islam. Namun melihat seiring berjalannya waktu terjadi pergeseran dari masa ke masa, baik dari proses kesepakatan sampai prosesi acaranya. Pertama, Penyebutan jumlah jujuran. Kedua, Proses kesepakatan. Ketiga, Pihak yang melakukan tradisi.Kata Kata Kunci : Barat dan Islam, Ontologi, Epistemologi, Aksiologi Sains.